2018
DOI: 10.1002/bse.2194
|View full text |Cite
|
Sign up to set email alerts
|

Examining the drivers and outcomes of corporate commitment to climate change action in European high emitting industry

Abstract: Climate change is a major strategic issue for firms that also has global environmental, social and economic implications. This paper draws upon quantitative survey research to examine the drivers and outcomes of corporate commitment to climate change action in European high emitting industry. More specifically, this research examines the significance of business drivers, sustainability drivers, and stakeholder pressure, in motivating corporate commitment to climate change action in such industry. It furthermor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
40
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(41 citation statements)
references
References 52 publications
(123 reference statements)
0
40
1
Order By: Relevance
“…A number of factors have been found to influence a company's readiness to be publicly engaged with climate change. Among them, size (C ordova et al, 2018;Eleftheriadis & Anagnostopoulou, 2015;Nartey, 2018;S anchez-Infante Hern andez et al, 2020), internal organisation systems (C ordova et al, 2018;Nartey, 2018;Rankin et al, 2011), international presence (Halkos & Skouloudis, 2016), the sector in which the companies operate (Weder et al, 2019), and external pressure (Haque & Islam, 2015;Littlewood et al, 2018), including media exposure (Wang et al, 2013) and extraordinary natural disasters (Pollach, 2018). Research also suggests that those companies and countries which implement environmental issues in their everyday practices, through patents or industrial and economic activity, tend to be more successful in terms of competitive advantages, economic growth and innovation (Ferreira et al, 2020;Mohammadi et al, 2018;Singh et al, 2019;Skare & Golja, 2012).…”
Section: Literature Reviewmentioning
confidence: 99%
“…A number of factors have been found to influence a company's readiness to be publicly engaged with climate change. Among them, size (C ordova et al, 2018;Eleftheriadis & Anagnostopoulou, 2015;Nartey, 2018;S anchez-Infante Hern andez et al, 2020), internal organisation systems (C ordova et al, 2018;Nartey, 2018;Rankin et al, 2011), international presence (Halkos & Skouloudis, 2016), the sector in which the companies operate (Weder et al, 2019), and external pressure (Haque & Islam, 2015;Littlewood et al, 2018), including media exposure (Wang et al, 2013) and extraordinary natural disasters (Pollach, 2018). Research also suggests that those companies and countries which implement environmental issues in their everyday practices, through patents or industrial and economic activity, tend to be more successful in terms of competitive advantages, economic growth and innovation (Ferreira et al, 2020;Mohammadi et al, 2018;Singh et al, 2019;Skare & Golja, 2012).…”
Section: Literature Reviewmentioning
confidence: 99%
“…A study conducted by Bansal and Roth (2000) revealed that three motivations, such as legitimation, competitiveness, and social/ecological responsibility, trigger corporate responsiveness. Boiral (2012) outlined the determinants of corporate commitment to reduce GHG emissions as business motivations, social and environmental motivations (defined as sustainability drivers by Littlewood et al 2018), and pressure from various stakeholders. Economic motivations are related to corporate competitiveness or potential financial benefits, which may result from the reduction of greenhouse gas emissions (Boiral 2012).…”
Section: Environmental Commitment and Disclosure Of Organizationsmentioning
confidence: 99%
“…The external stakeholder list continues with business associations, professional associations and chambers of commerce, financial markets and insurance companies, environmental groups, and local and national experts (Boiral 2012;Ali and Rizwan 2013;Murillo-Luna et al 2008). Significant internal stakeholders are employees, management, leaders, and company headquarters (Littlewood et al 2018). Murillo-Luna et al (2008) classified the large number of stakeholders who demand companies to protect the environment into five groups: regulatory stakeholders and corporate government stakeholders are the groups that managers are most concerned about.…”
Section: Environmental Commitment and Disclosure Of Organizationsmentioning
confidence: 99%
See 1 more Smart Citation
“…,Jones et al (2017),Latan et al (2018), X Li and Hamblin (2016),Linnenluecke and Griffiths (2010),Littlewood et al (2018),Longoni and Cagliano (2018),Lozano (2015),Lozano and von Haartman (2018),Kabongo and Boiral (2017),Khan et al (2018),Kitsikopoulos et al (2018),Maak et al (2016),Mangla et al (2017,Martens and Carvalho (2016),. I. K Mitchell and Walinga (2017),.…”
mentioning
confidence: 99%